Clustering of infant mortality within families in rural Burkina Faso - Kynast-Wolf, Gisela; Schoeps, Anja; Winkler, Volker; Stieglbauer, Gabriele; Müller, Olaf; Becher, Heiko (The American journal of tropical medicine and hygiene, 2019)
Abstract. In this study, we analyze clustering of infant deaths within families living in a rural part of western Burkina Faso. The study included 9,220 infants, born between 1993 and 2009 in Nouna Health and Demographic Surveillance System (HDSS). A clustering of infant deaths in families was explored by calculating observed versus expected number of infant deaths within families for a given family size. In addition, risk ratios were calculated for infant death depending on the vital status of the previous sibling. We observed 470 infant deaths, yielding an overall infant mortality risk of 51/1,000 births. Clustering of infant deaths within families was observed (P = 0.004). In smaller families, the mortality of firstborns was higher than for the following siblings. The infant mortality risk was higher when the preceding sibling died in infancy (P = 0.03). The study supports the hypothesis of infant death clustering existing within rural families in West Africa. Further studies are needed to shed more light on these findings with the goal to develop effective interventions directed toward the families who already lost a child.
Published online : 19 November 2018
Gesehen am 26.07.2019